The Bay of Biscay: Almost two centuries inspiring global oceanography. (5th February 2023) - Arias, Andrés; Ríos, Pilar; Cristobo, Javier; Paxton, Hannelore
Abstract: This Special Issue (SI) of Estuarine, Coastal and Shelf Science presents contributions from ISOBAY 17: the XVII International Symposium on the Oceanography of the Bay of Biscay. The main objective of this SI is to gather recent multidisciplinary research about the Bay of Biscay, covering different aspects from biological oceanography to marine geology and marine resources or habitat restoration and conservation. This SI aims as well to serve as a presentation platform for the most up to date scientific knowledge relating to the Bay of Biscay, from the open ocean and the deep sea to its coastal zone, and its transitional waters (estuaries, lagoons, and deltas). This common focus allowed a multidisciplinary approach in a wide range of disciplines, from biological oceanography to marine geology and integrative assessment of the marine environment. The contributing authors have explored a wide variety of these issues. The 24 selected articles provide a representative overview of the investigations carried out in this particular bay and cover the diversity of threats and opportunities faced by the marine environment of the Bay of Biscay and the people it supports. These investigations constitute a significant contribution towards an integrated knowledge of the Bay of Biscay and, hopefully, will serve as a basis for an integrative management of this region by a multi-disciplinary community of researchers, educators, and practitioners. Highlights: This SI presents contributions of the XVII International Symposium on Oceanography of Bay of Biscay. 24 selected articles providing a representative overview of most up to date investigations. Investigations from open ocean and deep sea to its coastal zone and transitional waters. Contributions covering the diversity of threats faced by marine environment and people it supports. Multidisciplinary contributions from different marine sciences and technologies.